Pratique # 21 : ConnectAînés / Francsavoir (pancanadienne) - Benoît, Josée; Michel, Jean Nephetaly (2021)

Profil des ressources des communautés francophones en milieu minoritaire - Deroche, Francine; Simard, Anne; Di Ruggiero, Erica; Levesque, Johanne (Reflets, 2007)
Le Réseau canadien de la santé (RCS) est une initiative nationale financée par Santé Canada. Le Réseau favorise l’accès à une information fiable, crédible et continuellement mise à jour, sur la santé et vient renforcer les réseaux existants de promotion de la santé. Le RCS a mené une enquête pour identifier quelles sont les informations disponibles sur la santé dans les communautés francophones vivant en milieu minoritaire. Il s’agit là d’un point de départ pour permettre au RCS de planifier et de mettre en œuvre des services en français pertinents. Les objectifs de l’enquête étaient: • d’identifier et d’établir le profil des organismes qui traitent de la santé des Francophones; • d’identifier les types d’organismes recommandés comme sources d’information aux consommateurs et consommatrices et aux intermédiaires de la santé; • d’identifier les ressources existantes les plus souvent demandées par les consommateurs et consommatrices et les intermédiaires de la santé et, • d’identifier les lacunes en matière d’informations sur la santé des francophones

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)
fs-ref-orig: Official Language Community Development Bureau. (2007). Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. Health Canada. fs-code-orig: Official Language Community Development Bureau-2007

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.